Engagement y fidelización del cliente en portales de noticias en Plus Tv, Riobamba - Riera Vargas, Karla Anahí (2026)
This research aims to determine the relationship between customer engagement and loyalty in news portals, specifically in the case of Plus TV, Riobamba's local digital media. In an environment of highly informative competence and fragmented content consumption, achieving an emotional, cognitive, and behavioral connection with the audience is a fundamental challenge for the media. For this, a quantitative methodology was applied, with a descriptive approach and a hypothetical-deductive method, using surveys administered to the city's economically active population. The results reveal that the portal offers certain programs, but to promote credibility, it is necessary to have advanced technology and a staff able to cover events such as live news, sports ads, and local entertainment content. That is, its programming is attractive to users. Chi-square analysis revealed a significant relationship between engagement and customer loyalty. Based on these findings, strategies are proposed focused on personalizing the user experience, strengthening the local identity of the environment, incorporating gamification elements, and promoting spaces for active participation. It is concluded that effective engagement improves the relationship with users but is also a determining factor in ensuring the sustainability and organic growth of local digital media.